TRADISI IKAT NAMA DI DESA HARAPAN KECAMATAN SUNGAI APIT KABUPATEN SIAK - Andrian, Raja Milki Nur; Rosaliza, Mita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study analyzes the Ikat Nama Tradition conducted by the people of Harapan Village, Sungai Apit District, Siak Regency. Using qualitative methods with purposive sampling technique to determine the informants, the authors determined 6 people of the Harapan Village community to become informants in order to provide an explanation of the Ikat Nama Tradition. The results of this study found that the procession of the Ikat Nama Tradition contained a series of events namely tahlilan, eating together and continued with the reading of marhaban and zanji. Binding the name is done at the time of tahlilan namely by reciting Al-Fatihah then witnessed by invited guests. The one who binds the name of the child is an ustadz or religious figure who has been trusted by those who have a purpose. Before the baby is born, parents ask advice from religious leaders for baby names that have good meanings and are taken from the Qur'an. The equipment used in the form of scissors, coconut, perfume, baby basket, and money has the meaning implied in it. In addition to equipment, each procession also implies meaning and as a form of interaction efforts from those who have an interest to invited guests. The people there still maintain this tradition because it has become a habit for a long time and indeed this tradition is a good habit and there is praise to Allah SWT so that people feel this habit has no loss if maintainedÂ Keywords: Traditions, Ikat Nama, Symbolic Meaning